Simulation and Analysis of Cascade Tripping & Islanding Detection: Analyzing Cascading Failure and Developing an Adaptive Islanding Scheme (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cascading failure occurs when an initial disturbance in power system propagates to cause blackouts. Large cascading failure is not frequent, but they have large risk due to their large loss of revenue. When a power system is subjected to large disturbances control actions need to be taken to steer the system away from severe results and to limit the extent of the disturbance. Analysis of cascading and islanding is divided into two steps (a)Detection of major disturbances leading to cascading events, which includes steady state, transient and dynamic analysis. (b)Adaptive Islanding scheme to develop a fast accurate assessment for detection of timing for conducting controlled islanding scheme that prevents cascading phenomena.